Blackwell handbook of infant development - Bremner, J. Gavin, 1949-; Fogel, Alan.; Wiley InterScience (Online service) (Malden, MA : Blackwell Pub., 2004)
This up-to-date overview of the fast-moving field of infant development covers all the major areas of interest in terms of research, applications and policy. Each of the 26 chapters is written by a leading international researcher and offers a current review of the theory and research findings in his or her particular area of expertise. The volume is divided into four sections on perception and cognition; social, emotional and communicative development; risk factors in development; and contexts and policy issues. Integration and coherence across the Handbook are provided by editorial commentaries prefacing each section.
Visual perception / Alan Slater -- Hearing, listening, and understanding : auditory development in infancy / Anne Fernald -- Action in infancy -- perspectives, concepts, and challenges : the development of reaching and grasping / Ad W. Smitsman -- Cognitive development : knowledge of the physical world / J. Gavin Bremner -- Infant learning and memory / Carolyn Rovee-Collier and Rachel Barr -- Functional brain development during infancy / Mark H. Johnson -- Origins of self-concept / Philippe Rochat -- Joint visual attention in infancy / George Butterworth -- Mind knowledge in the first year : understanding attention and intention / Vasudevi Reddy -- Mother-infant interaction / Marc H. Bornstein and Catherine S. Tamis-LeMonda -- First attachments : theory and research / Dymphna van den Boom -- Peers and infant social/communicative development / Carol O. Eckerman and Karen Peterman -- The salience of touch and physical contact during infancy : unraveling some of the mysteries of the somesthetic sense / Dale M. Stack -- Preverbal communication / Andrew Lock -- Early language / Luigia Camaioni -- Principles of emotion and its development in infancy / David C. Witherington, Joseph J. Campos, and Matthew J. Hertenstein -- Temperament / Theodore D. Wachs and John E. Bates -- Prenatal development and risk / William P. Fifer, Catherine E. Monk, and Jill Grose-Fifer -- Early intervention and risk / Douglas R. Powell -- Early social development in young children with autism : theoretical and clinical implications / Sally Ozonoff and Mikle South -- Infant mental health in a changing society / Donna M. Gelfand -- Sensory deficits / Gunilla Preisler -- Infancy research, policy, and practice / Marguerite Barratt -- Childcare research at the dawn of a new millennium : taking stock of what we know / Sarah L. Friedman, Suzanne Randolph, and Anita Kochanoff -- Health, nutrition, and safety / Jeanne Thibo Karns -- The history (and future) of infancy / Alan Fogel.
Includes bibliographical references and indexes.
Print version record.
Keywords: Infants -- Development -- Handbooks, manuals, etc; Infants -- Health and hygiene -- Handbooks, manuals, etc; Infants -- Development; Infants -- Health and hygiene; Electronic books; Handbooks and manuals